2015
DOI: 10.1007/s10827-015-0585-1
|View full text |Cite
|
Sign up to set email alerts
|

Cortical neuron activation induced by electromagnetic stimulation: a quantitative analysis via modelling and simulation

Abstract: Previous simulation works concerned with the mechanism of non-invasive neuromodulation has isolated many of the factors that can influence stimulation potency, but an inclusive account of the interplay between these factors on realistic neurons is still lacking. To give a comprehensive investigation on the stimulation-evoked neuronal activation, we developed a simulation scheme which incorporates highly detailed physiological and morphological properties of pyramidal cells. The model was implemented on a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 52 publications
4
44
0
Order By: Relevance
“…However, these attempts had various limitations. First, in early studies no anatomical information on large-scale brain morphology was applied 2325 . Rather than constructing a finite element head model, these studies applied a uniform electric field to the neuronal model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, these attempts had various limitations. First, in early studies no anatomical information on large-scale brain morphology was applied 2325 . Rather than constructing a finite element head model, these studies applied a uniform electric field to the neuronal model.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while we lengthened PNs to fit the cortex, the uncertainties regarding morphology of neurons was not fully studied. Wu et al (2016) incorporated a multitude of PNs with various stimuli 25 and Salvador et al (2010) constructed various types of neural structures including pyramidal neurons, interneurons, and association fibers 29 ; they found that the excitability can be shaped by field orientation, pulse wave form, and diameter of neurons. In addition, changes in the electrical properties, such as membrane properties and ion channels had the largest influence on neuronal excitability 25 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations